Convolutional Neural Network Feature Reduction using Wavelet Transform - Levinskis, A. (Elektronika ir Elektrotechnika, 2013)
Paper describes wavelet transform possible application for convolutional neural networks (CNN). As it already known, wavelet transform gives good signal representation in time and frequency domains. This can be useful for CNN input feature reduction as well as architecture simplicity by using only part of coefficients. The result of work is set of experiment which enables to configure out the most appropriate coefficient part. After feature reductions and architecture simplicity achieved configuration could classify data almost ten times faster than original. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3698